Development of a smartphone app for adolescents with lupus: a collaborative meeting-based methodology inclusive of a wide range of stakeholders - Jessica Herschman; Todd Kasenberg; Deborah Levy; Natasha Ruth; Christy Taberner; Miriam Kaufman; Andrea Regina (Pan American Health Organization, 2014)
Traditional challenges of creating a medical app include hearing the voices of various stakeholders as a collective rather than in a consultative process that is sequential. This report describes the development of a mobile (smartphone) app for adolescents with lupus as well as the process that was used to overcome the challenge described above. The development of the smartphone app addressed optimal ways to incorporate information about 1) lupus, including the effects of both the disease and the medications used to treat it; 2) how life choices can affect lupus patients' condition; and 3) ways to increase self-management and communication. The collaborative concept-generating and requirements-gathering methodology was used during a two-day workshop with a range of stakeholders (ages 16 - 59 years) that focused on leveraging user-centered design methods to generate guidance to mobile app developers. The app development process conducted during the workshop included the following steps: 1) recruiting a goal-focused collaborative group, 2) defining app objectives, 3) evaluating potential needs of users, 4) brainstorming app features and use-case modeling, 5) reviewing existing app features and prototypes, 6) refining functionalities, 7) writing user narratives, 8) visualizing navigation and feature design, and 9) identifying content. The use of creative devices such as drawing interfaces fostered fun, engagement, and sustained energy, and the use of a brainstorming technique leveraged methods that ensured an inclusive process so that even participants who were shy, quiet, or easily intimidated by "professionals" felt confident to contribute. In addition to a name change for the app, project outcomes included the selection of the following app features: symptom tracking; appointment and medication reminders; a social media component; a medical summary; easy navigation; informational content; gamification; and personalization (options for customization).